2005
DOI: 10.1038/sj.jea.7500447
|View full text |Cite
|
Sign up to set email alerts
|

Ambient fine particles modify heart rate variability in young healthy adults

Abstract: Particulate air pollution has been related with cardiopulmonary morbidity and mortality. Recent studies have shown that an increase in particulate matter (PM) 2.5 ambient concentrations was associated with a decrease in heart rate variability (HRV) in the elderly with cardiovascular conditions, which could increase the risk of death. In order to assess if this association could also be observed in young adults, we studied 40 young healthy residents of the Mexico City Metropolitan Area (MCMA) who underwent 13 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 28 publications
(43 reference statements)
6
44
1
Order By: Relevance
“…PM consists of multiple chemical species present together. Fine particles with an aerodynamic diameter of 2.5 micrometers (µm) or less (PM 2.5 ), in particular, have been linked to adverse health impacts such as cardiovascular (Pope et al, 2004;Henneberger et al, 2005;Namdeo and Bell, 2005;Pope and Dockery, 2006;Vallejo et al, 2006;Neuberger et al, 2007;Bell et al, 2008;Ren and Tong, 2008;Atkinson et al, 2014;Grahame et al, 2014) and respiratory diseases (Vedal, 1997;Pope and Dockery, 2006;Ren and Tong, 2008;Delfino et al, 2009;Sinclair et al, 2013;Atkinson et al, 2014;Jones et al, 2014). While specific components of PM 2.5 are believed to be important drivers of health effects (Grahame et al, 2014), particularly of shortterm health effects (Rohr and Wyzga, 2012), it is still unclear whether any single component is responsible for the health effects, or whether the species serve as an indicator for other pollutants (Rohr and Wyzga, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PM consists of multiple chemical species present together. Fine particles with an aerodynamic diameter of 2.5 micrometers (µm) or less (PM 2.5 ), in particular, have been linked to adverse health impacts such as cardiovascular (Pope et al, 2004;Henneberger et al, 2005;Namdeo and Bell, 2005;Pope and Dockery, 2006;Vallejo et al, 2006;Neuberger et al, 2007;Bell et al, 2008;Ren and Tong, 2008;Atkinson et al, 2014;Grahame et al, 2014) and respiratory diseases (Vedal, 1997;Pope and Dockery, 2006;Ren and Tong, 2008;Delfino et al, 2009;Sinclair et al, 2013;Atkinson et al, 2014;Jones et al, 2014). While specific components of PM 2.5 are believed to be important drivers of health effects (Grahame et al, 2014), particularly of shortterm health effects (Rohr and Wyzga, 2012), it is still unclear whether any single component is responsible for the health effects, or whether the species serve as an indicator for other pollutants (Rohr and Wyzga, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have observed that elevated PM exposure is associated with changes in autonomic function as indicated by changes in HRV (measured in time and frequency domains) in young healthy subjects (Riediker et al, 2004 ;Vallejo et al, 2006 ;Adar et al, 2007 ;Chuang et al, 2007 ;Riediker, 2007 ;Samet et al, 2007 ;C á rdenas et al, 2008 ). In most of the studies, measures of HRV were reduced, suggesting an overall trend toward withdrawal of parasympathetic tone.…”
Section: Who I S Susceptible To Pm -Induced Ans Changes?mentioning
confidence: 96%
“…As examples see: Gong et al, 2005;Fung et al, 2006;Martins et al, 2006;Sarnat et al, 2006;or Vallejo et al, 2006. The workgroup also considered that an immune-compromised adult may suffer substantially greater adverse effects from exposure to the same level of contaminant than his or her healthy counterpart, but did not identify a study to confirm this.…”
Section: Findings On the Key Issuesmentioning
confidence: 99%